Quasi-Static Optical Coherence Elastography to Characterize Human Corneal Biomechanical Properties - Kling, Sabine (Invest Ophthalmol Vis Sci, 2020)
PURPOSE: Quasi-static optical coherence elastography (OCE) is an emerging technology to investigate corneal biomechanical behavior in situations similar to physiological stress conditions. Herein OCE was applied to evaluate previously inaccessible biomechanical characteristics of human corneal tissue and to study the role of Bowman's layer in corneal biomechanics. METHODS: Human corneal donor buttons (n = 23) were obtained and Descemet's membrane and endothelium were removed. In 11 corneas, Bowman's layer was ablated by a 20 µm stromal excimer laser ablation. Buttons were mounted on an artificial anterior chamber and subjected to a pressure modulation from 10 to 30 mm Hg, and back to 10 mm Hg, in steps of 1 mm Hg. At each step, a spectral-domain optical coherence tomography scan was obtained. Displacements were analyzed by optical flow tracking, and strain over the entire stromal depth was retrieved from the phase gradient of the complex interference signal. RESULTS: During pressure increase, corneal tissue moved upward (486–585 nm/mm Hg) but did not fully recover (Δ= 2.63 to 8.64 µm) after pressure decrease. Vertical corneal strain distribution was negative in the anterior and positive in the posterior cornea, indicating simultaneous corneal compression and expansion, respectively. Bowman's layer caused minor localized differences in corneal strain distribution. CONCLUSIONS: Corneal strain distribution is more complex than previously assumed, with a fundamental difference in mechanical response between the anterior and posterior stroma. Clinically, OCE technology might be used to monitor the progression of corneal ectatic diseases and to determine the success of corneal cross-linking.